1988
DOI: 10.1002/fld.1650080905
|View full text |Cite
|
Sign up to set email alerts
|

Dirichlet and Neumann boundary conditions for the pressure poisson equation of incompressible flow

Abstract: SUMMARYIn a recent paper Gresho and Sani' showed that Dirichlet and Neumann boundary conditions for the pressure Poisson equation give the same solution. The purpose of this paper is to confirm this (for one case at least) by numerically solving the pressure equation with Dirichlet and Neumann boundary conditions for the inviscid stagnation point flow problem. The Dirichlet boundary condition is obtained by integrating the tangential component of the momentum equation along the boundary. The Neumann boundary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The issue of the correct boundary condition to assign to the pressure was also studied by many other authors. Among them Gresho and Sani [22], (see also [39], [1]) showed that Dirichlet and Neumann boundary conditions for the pressure give the same solution. In fact they recover appropriate Dirichlet boundary conditions for the pressure by taking into account the normal derivative of the pressure associated with the Neumann boundary condition and by using Green's functions.…”
Section: Approximating System and Main Resultsmentioning
confidence: 99%
“…The issue of the correct boundary condition to assign to the pressure was also studied by many other authors. Among them Gresho and Sani [22], (see also [39], [1]) showed that Dirichlet and Neumann boundary conditions for the pressure give the same solution. In fact they recover appropriate Dirichlet boundary conditions for the pressure by taking into account the normal derivative of the pressure associated with the Neumann boundary condition and by using Green's functions.…”
Section: Approximating System and Main Resultsmentioning
confidence: 99%
“…We demonstrated with examples the core principles of this method, and how it can be applied to specific problems in physics. Furthermore, this model can be optimized, and adapted for a wide range of systems (see [1] and [2]). This, coupled with the easy access to the needed resources, makes the relaxation method and its applications an excellent topic to introduce numerical methods for solving physical problems.…”
Section: Discussionmentioning
confidence: 99%
“…which means that the average value of the solution over a sphere is equal to the function evaluated at its center 1 .…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…For method (i), all the boundary conditions are satisfied through the groupings described in section (3); no additional numerical boundary conditions are required. In method (ii), the boundary conditions are satisfied through similar groupings, as portrayed in Fig.3.…”
Section: Boundary Condltionsmentioning
confidence: 99%